Keap1-Nrf2 Heterodimer: A Therapeutic Target to Ameliorate Sickle Cell Disease - Waseem Chauhan; Rahima Zennadi (MDPI AG, 2023)
Sickle cell disease (SCD) is a monogenic inheritable disease characterized by severe anemia, increased hemolysis, and recurrent, painful vaso-occlusive crises due to the polymerization of hemoglobin S (HbS)-generated oxidative stress. Up until now, only four drugs are approved for SCD in the US. However, each of these drugs affects only a limited array of SCD pathologies. Importantly, curative therapies, such as gene therapy, or hematopoietic stem cell transplantation are not available for every patient because of their high costs, availability of donor matching, and their serious adverse effects. Therefore, there is an unmet medical need for novel therapeutic strategies that target broader SCD sequelae. SCD phenotypic severity can be alleviated by increasing fetal hemoglobin (HbF) expression. This results in the inhibition of HbS polymerization and thus sickling, and a reduction in oxidative stress. The efficacy of HbF is due to its ability to dilute HbS levels below the threshold required for polymerization and to influence HbS polymer stability in RBCs. Nuclear factor-E2-related factor 2 (Nrf2)/Kelch-like ECH-associated protein-1 (Keap1)-complex signaling is one of the most important cytoprotective signaling controlling oxidative stress. Nrf2 is present in most organs and, after dissociation from Keap1, it accumulates in the cytoplasm, then translocates to the nucleus where it binds to the antioxidant response element (ARE) sequences and increases the expression of various cytoprotective antioxidant genes. Keeping this in mind, various researchers have proposed a role of multiple agents, more importantly tert-Butylhydroquinone (tBHQ), curcumin, etc., (having electrophilic properties) in inhibiting keap1 activity, so that Nrf2 can translocate to the nucleus to activate the gamma globin gene, thus maintaining alpha-hemoglobin-stabilizing protein (AHSP) and HbF levels. This leads to reduced oxidative stress, consequently minimizing SCD-associated complications. In this review, we will discuss the role of the Keap-1-Nrf2 complex in hemoglobinopathies, especially in SCD, and how this complex might represent a better target for more effective treatment options.